2012
DOI: 10.2214/ajr.12.8576
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic Evaluation of Subclinical Entheseal Involvement in Patients With Behçet Disease

Abstract: This is the first study to our knowledge to show significant subclinical enthesopathy of the triceps tendon enthesis in patients with Behçet disease who had no arthritic involvement. These data suggest that the Madrid sonography enthesitis index scoring system for sonographic detection of enthesopathy should be incorporated into the clinical protocol for evaluating patients with Behçet disease in routine clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 13 publications
(28 reference statements)
0
10
0
Order By: Relevance
“…In literature, in addition to SpA, enthesitis was investigated only in few diseases including Behçet's disease [24,25], familial Mediterranean fever [26,27], Sjögren syndrome [28], dialysis patients [29], fibromyalgia [30,31], psoriasis [9,32], inflammatory bowel disease without spondyloarthritis symptoms [33] by using US. Although musculoskeletal involvement in SSc was investigated in a few studies by using US [34][35][36] with SSc by using MRI [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In literature, in addition to SpA, enthesitis was investigated only in few diseases including Behçet's disease [24,25], familial Mediterranean fever [26,27], Sjögren syndrome [28], dialysis patients [29], fibromyalgia [30,31], psoriasis [9,32], inflammatory bowel disease without spondyloarthritis symptoms [33] by using US. Although musculoskeletal involvement in SSc was investigated in a few studies by using US [34][35][36] with SSc by using MRI [7].…”
Section: Discussionmentioning
confidence: 99%
“…However, we believe that the use of predefined sonographic criteria and cut-offs (even though developed for patients with SpA and stil not validated for SSc) may partly overcome this limitation. The use of these predefined cut-offs may also be argued, but this was the only possible approach to document enthesitis in SSc and used to assess enthesitis in other diseases as well [24,29,31,33,41]. We also calculated our own normotive data in healthy women in order to obtain more robust comparisons and document differences in tendon/ligament thicknesses as an important component in the diagnosis of enthesitis and calculating the MASEI.…”
Section: Discussionmentioning
confidence: 99%
“…However, GUESS has several limitations for evaluation of entheseal sites, as mentioned above. Therefore, the MASEI scoring system and also its cutoff value may be modified for nonspondyloarthropathy disorders such as familial Mediterranean fever and Behçet disease 23 …”
Section: Discussionmentioning
confidence: 99%
“…Tendonitis improved after administering an injection of triamcinolone. While joint involvement in Behcet's disease is usually non-erosive synovitis in large joints, the present case showed that Behcet's disease can induce tendonitis in small joints ( 1 , 2 ).…”
mentioning
confidence: 45%